Does Medicaid Hcbs Generosity Influence Nursing Home Placement for Dually Eligible Adrd Patients?. (20th August 2020) - Wang, S.; Yan, D.; Temkin‐Greener, H.; Cai, S.
Abstract : Research Objective: Older adults with Alzheimer's disease and related dementias (ADRD) often receive informal care to support their community living. As the disease progresses, the physical and emotional toll it exacts on caregivers may become unsustainable, and nursing home (NH) placement may become necessary. Medicaid Home and Community‐Based Services (HCBS) programs provide various types of services to support community living for Medicaid enrollees, which may reduce or delay NH placement for ADRD patients. This study aimed to examine the relationship between Medicaid HCBS generosity and the likelihood of NH placement for duals with ADRD, and their level of functional impairment at NH admission. Study Design: National Medicare data, Medicaid Analytic eXtract (MAX), and MDS 3.0 for CY2010‐2013 were linked. Eligible Medicare‐Medicaid dual beneficiaries with ADRD were identified and followed for up to a year. Based on MAX data, two measures of HCBS generosity were constructed at the county level for older duals with ADRD: (a) breadth (ie, proportion of duals who used HCBS services); and (b) intensity (ie, average HCBS spending per user). Outcomes included NH placement during the follow‐up year (dichotomous) and the level of physical impairment (ie, activities of daily living [ADL, 0‐28 point scale], categorized into low, moderate, and severe impairment) at the time of NH admission. A linear probability model with county random‐effects and robust standard errors was estimated to examine the relationship between the likelihood of NH placement and HCBS generosity, accounting for individual (eg, sociodemographic characteristic, prior hospitalizations, and comorbidities) and county‐level covariates (eg, median household income, female labor participation). A multinomial logistic model was estimated to examine the relationship between HCBS generosity and ADL impairment among those who were admitted to NHs. Population Studied: Community‐dwelling older dual beneficiaries with ADRD who were enrolled in fee‐for‐service Medicaid between October 1, 2010, and December 31, 2012 (N = 365 310). Principal Findings: Considerable variation in county‐level HCBS breadth and intensity was observed. 17.1% of duals with ADRD had NH placement within one year. After accounting for individual and county level covariates, we found that a 10 percentage‐point increase in HCBS breadth among individuals with ADRD was associated with 1.1 percentage point reduction ( P < 0.01) in the likelihood of NH placement. Among individuals with NH placement, greater HCBS intensity was related to a higher level of impairment at NH admission (100 increase in HCBS intensity led to 1.03 and 1.04 times the likelihood of having moderate or severe physical impairment [ P < 0.01]). Greater HCBS breadth was associated with less physical impairment (10 percentage‐point increase led to 0.93 and 0.91 times the likelihood of having moderate or severe physical impairment [ P < 0.01]). Conclusions: Among community‐dwelling duals with ADRD, Medicaid HCBS breadth was associated with a lower likelihood of NH placement, and HCBS intensity was associated with greater physical impairment at NH admission. Implications for Policy or Practice: Investment in Medicaid HCBS may prevent or delay NH placement among community‐dwelling older adults with ADRD. More research is needed to identify how the utilization of different HCBS services may affect NH placement. Primary Funding Source: National Institutes of Health.